Preliminary assessment on land surface temperature map and slope stability at Jelutong landfill - Aie, Nyemas Dewi Pramita (2019)
This project report presents preliminary assessment on land surface temperature (LST) map and slope stabilization of Jelutong landfill. Due to increasing waste produced every day, poor management of waste disposal will create more problem such as health risks and poor quality of environment. A well-designed landfill should be able to contain harmful waste by-products such as leachate, gases and heat from entering the ground or expose to the air and surrounding. Unmanned Aerial Vehicles (UAVs) are used to captured aerial view of the landfill and thermal infrared camera is used to detect the infrared range that produced warm objects stand out well against cooler backgrounds. Ground data sampling such as ground temperature also conducted to compare with hot spot detected in LST map. Leakage of gases also detected using gas detector with known concentration. In addition, the stability of landfill slopes is analysed using Slope/W Geostudio software to obtain its factor of safety (FOS). Two type of analysis method are used which are Mongerstern – Price analysis method and simplified Bishop’s method to compare the results. The results obtained, and observation made in this study suggests that the integration of UAV with thermal imaging camera, respectively can be used to address this problem by monitoring the thermal signature of these waste sites and locate hotspots. The certain landfill slope stability is found to be unsafe and need to be avoided.